ANALISIS KEBUTUHAN AIR TANAMAN SELADA (Lactuca sativa L.) PADA INCEPTISOL DAN VERTISOL BERBASIS INTERNET OF THINGS (IoT) - Yayan Poga; Nurdin Nurdin; Wawan Pembengo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Lactuca sativa L. has good economic prospects, but lettuce production often declines due to the unmet water requirement of lettuce. This study aimed to determine the water needs of lettuce on Inceptisol and Vertisol based on the Internet of Things (IoT). The location study was in the green house, Huluduotamo Village, Bone Bolango Regency, from September to October 2021, while the Vertisol and Inceptisol samples were from Sidomukti Village, Gorontalo Regency. This study used the Penman method with the Cropwat 8.0 application which was integrated with a smartphone through the Blynk (IoT) application. The water requirement yield of lettuce plants in September on Vertisol and Inceptisol in the early phase was 2.45 mm/day, the middle phase was 3.73 mm/day, and the final phase was 3.54 mm/day. Soil moisture detection device at field capacity moisture content produces 319 Analog Digital Converter (ADC) and soil in moist conditions reaches 534 ADC. The analog data value of the water content of the Inceptisol field capacity is 343 ADC and the soil in a moist state is 574 ADC. The performance of the device for detecting soil moisture in the water condition of the 15% field capacity of Vertisol and 22% Inceptisol is more effective than the gravimetric method.